2023
DOI: 10.1021/acssuschemeng.2c07285
|View full text |Cite
|
Sign up to set email alerts
|

Green Thermo-Photo Catalytic Production of Syngas Using Pd/Nb–TiO2 Catalysts

Abstract: In this contribution, a series of Pd-promoted Nb-doped titania samples were essayed in the gas-phase thermo-photo production of syngas from methanol/water mixtures. The Pd loading was tested in the 0.1 to 2.5 wt % range, leading to the presence of metallic nanoparticles under reaction. Reaction rates exceeding 52 mmol H2 g–1 h–1 and quantum efficiencies above 33% were obtained. The optimum sample having a 0.5 wt % of Pd provided an outstanding synergy between light and heat under reaction conditions, facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Nonetheless, their wide band gaps result in the absorption of only a small portion of the solar spectrum, severely limiting solar energy conversion efficiency. 122,123 Recent studies have demonstrated that introducing oxygen vacancies can lead to the creation of transition state energy levels, thereby narrowing the band gap and enhancing light absorption capacity. However, these oxygen vacancies can also introduce lattice distortions and alter spatial polarity, hindering the efficient transport of photogenerated carriers and reducing photocatalytic efficiency.…”
Section: Challenges and Difficulties Of Dual-functional Photocatalystmentioning
confidence: 99%
“…Nonetheless, their wide band gaps result in the absorption of only a small portion of the solar spectrum, severely limiting solar energy conversion efficiency. 122,123 Recent studies have demonstrated that introducing oxygen vacancies can lead to the creation of transition state energy levels, thereby narrowing the band gap and enhancing light absorption capacity. However, these oxygen vacancies can also introduce lattice distortions and alter spatial polarity, hindering the efficient transport of photogenerated carriers and reducing photocatalytic efficiency.…”
Section: Challenges and Difficulties Of Dual-functional Photocatalystmentioning
confidence: 99%